BASLAWÍSH KLASLARDA IMKANIYATÍ SHEKLENGEN BALALARDÍŃ HUQÍQLARÍN QORǴAWDÍ KEPILLIKLEW - Jamgırbaeva, N. (SCIENCE and SOCIETY, 2022)
Children with disabilities are an important layer of society that requires special attention. The article, using the example of inclusive education, will analyze the issues of social protection of children with disabilities in Uzbekistan, the regulatory legal acts adopted in this regard, the conditions created.